Convention on Cooperation in the Northwest Atlantic Fisheries, Ottawa, 24 October 1978 : (Consolidated version including the following amendments to the Convention made on 1 January 1980, 9 October 1987, 13 September 1996 and 18 May 2017) /: (Consolidated version including the following amendments to the Convention made on 1 January 1980, 9 October 1987, 13 September 1996 and 18 May 2017). ([2019-02-08]) - Unknown
No abstract available